DESKRIPSI EFEK SAMPING OBAT ANTI TB PADA PASIEN TB YANG SEDANG MENJALANI PENGOBATAN TB DI PUSKESMAS HARAPAN RAYA PEKANBARU - Trisiwi Kusuma Ningrum; Mailur Rahmi (LPPM Universitas Abdurrab, 2020)
ABSTRACT Tuberculosis (TB) is an infectious disease that must get special treatment with antibiotics given at least 6 months. The use of anti-TB drugs with various types of drugs and a long duration can cause complaints of side effects. This study aims to determine the side effects of anti-TB drugs in TB patients who are treating TB treatment at the health center. This research is descriptive with 35 respondents. The data collection method used a questionnaire and was carried out on 18 June-18 July 2019. The results showed that 27 respondents (77.1%) experienced side effects of anti-TB oabat, while only 8 respondents (22.9%) had no complaints. The most common complaints experienced by TB sufferers during treatment were complaints of tingling and burning sensation in the legs of 13 people (37.1%) and followed by other side effects in the form of no appetite as many as 6 respondents (17.1), joint pain as many as 9 respondents ( 25.7), redness in urine (urine) by 8 respondents (22.9), itching and redness on the skin by 11 respondents (31.4), impaired balance by 6 respondents (17.1), icterus without other causes by 4 respondents (11.4), visual impairment as many as 6 respondents (17.1), purpura and climbing (shock) as much as 1 respondent (2.9). Keywords: Side Effects, Anti-TB drugs